Pengaruh Media Sosial dan Teman Sebaya terhadap Perilaku Konsumtif MAN 2 Bukittinggi - Imelda; Alfi Rahmi (YASIN, 2026)
The increase in students’ consumptive behavior is associated with the high intensity of social media use and strong interactions with peers. This study aimed to analyze the partial and simultaneous effects of social media and peers on the consumptive behavior of students at MAN 2 Bukittinggi. The study employed a quantitative approach with an associative research design. The research sample comprised 188 students selected through proportional random sampling. Data were collected using a questionnaire and analyzed through simple linear regression and multiple linear regression with the assistance of SPSS. The results showed that social media had a positive and significant effect on consumptive behavior, with a contribution of 52.3%, whereas peers had a positive and significant effect, with a contribution of 49.2%. Simultaneously, social media and peers had a positive and significant effect on consumptive behavior, with a contribution of 61.6%. The regression equation Y = 13.588 + 0.583X₁ + 0.568X₂ indicates that social media had a slightly more dominant effect than peers. These findings confirm that the higher the intensity of social media use and the stronger the influence of peers, the greater the tendency toward consumptive behavior among students. This study provides practical implications for schools, teachers, and parents to strengthen students’ digital literacy, financial literacy, and self-control through integrated guidance to minimize consumptive behavior.